Highly Reliable Memory Architecture Using Adaptive Combination of Proactive Aging-aware In-Field Self- Repair and ECC - Mayuga, Gian (Archīum Ateneo, 2019)
Reliability of embedded memory is critical for SoCs. Aging-induced faults manifest in field, and they affect the reliability of embedded memories which occupy the most area of a SoC. By performing a proactive approach that repairs aged memory words in use, the probability of fault occurrence should be minimized. In this work, we proposed an in-field strategy that proactively repairs aged words as well as correctable words. The reliability is enhanced further by combining an aging test, an in-field repair, and an error correction technique. An adaptive reconfiguration of the memory words, including aged words, correctable words and uncorrectable words, is implemented with small overhead. A 3-state model that identifies memory cells as healthy, aged or faulty is newly introduced, and the reliability evaluation using this model demonstrates the effectiveness of the proposed strategy.